Passive performance and building form: An optimization framework for early-stage design support. (February 2016) - Konis, Kyle; Gamas, Alejandro; Kensek, Karen
Highlights: Presents a new method to improve performance of passive strategies in early design. Form finding to achieve daylighting and whole building energy optimization. Automatically incorporates local urban geometry in simulation process. Case study application in four diverse climates and real urban sites. Solutions exceed performance of current high performance building reference. Abstract: To achieve low and zero net energy performance objectives in buildings, designers must make optimal use of passive environmental design strategies. The objective of this research is to demonstrate the application of a novel Passive Performance Optimization Framework (PPOF) to improve the performance of daylighting, solar control, and natural ventilation strategies in the early design stages of architectural projects. The PPOF is executed through a novel, simulation-based parametric modeling workflow capable of optimizing building geometry, building orientation, fenestration configurations, and other building parameters in response to program requirements, site-specific building adjacencies, and climate-based daylighting and whole-building energy use performance metrics. The applicability of the workflow is quantified by comparing results from the workflow to an ASHRAE 90.1 compliant reference model for four different climate zones, incorporating real sites and urban overshadowing conditions. Results show that the PPOF can deliver between a 4% and 17% reduction in Energy Use Intensity (EUI) while simultaneously improving daylighting performance by between 27% and 65% depending on the local site and climatic conditions. The PPOF and simulation-based workflow help to make generative modeling, informed by powerful energy and lighting simulation engines, more accessible to designers working on regular projects and schedules to create high-performance buildings.